2021
DOI: 10.3390/ijerph18168526
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Emotional Responses to the Spatial Quality of Urban Green Spaces through Self-Report and Face Recognition Measures

Abstract: Although creating a high-quality urban green space (UGS) is of considerable importance in public health, few studies have used individuals’ emotions to evaluate the UGS quality. This study aims to conduct a multidimensional emotional assessment method of UGS from the perspective of spatial quality. Panoramic videos of 15 scenes in the West Lake Scenic Area were displayed to 34 participants. For each scene, 12 attributes regarding spatial quality were quantified, including perceived plant attributes, spatial st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…Nature-based tourism activities can play a crucial role in mitigating socio-emotional distress, thanks to the natural environment's capacity to restore mental resources [11]. The study of human emotional response to different natural stimuli is not new to psychology literature [27][28][29][30], and it has been shown that exposure to natural environments can trigger positive emotions [31,32] and induce feelings of calmness [33]. Research on forest bathing and forest therapy has ascertained that during forest immersions, people tend to experience decreased negative feelings, such as depression, anger, and fatigue, and increased positive emotions that can be maintained over time [34,35].…”
Section: Emotionsmentioning
confidence: 99%
“…Nature-based tourism activities can play a crucial role in mitigating socio-emotional distress, thanks to the natural environment's capacity to restore mental resources [11]. The study of human emotional response to different natural stimuli is not new to psychology literature [27][28][29][30], and it has been shown that exposure to natural environments can trigger positive emotions [31,32] and induce feelings of calmness [33]. Research on forest bathing and forest therapy has ascertained that during forest immersions, people tend to experience decreased negative feelings, such as depression, anger, and fatigue, and increased positive emotions that can be maintained over time [34,35].…”
Section: Emotionsmentioning
confidence: 99%
“…Many studies deal with the quality and direct impact of urban green spaces, the parameterization of the visual evaluation and perception of space (Chen et al, 2019;Qiao et al, 2021;Sun et al, 2023), with the visual complexity levels of streets and the perceived safety and comfort of users (Kawshalya et al, 2022), or with multivariate modelling of the street space based on computer analytics (Wang et al, 2023). The more intensive use of pedestrian streets by both local residents and tourists is indisputable.…”
Section: Introductionmentioning
confidence: 99%